Dampak Perilaku Maladaptif Bagi Anak yang Dijadikan Pengemis oleh Orang Tua Sebagai Bentuk Eksploitasi Di Makam KH. Syekh Asnawi Caringin - Ati Sumiyati; Sholih Sholih; Alfiandy Warih Handoyo (CV. Syntax Corporation Indonesia, 2021)
Exploitation is generally carried out in big cities. This is no exception also happened in the pilgrimage tourism area of ​​KH's tomb. Sheikh Asnawi. This study aims to determine the description of exploitation carried out by parents to make children as beggars in the tourist area of ​​​​KH's grave. Sheikh Asnawi by looking at the maladaptive behavior caused by exploitation, knowing the factors that cause children to be exploited by their parents, and knowing the service efforts that can be provided to reduce maladaptive behavior from victims of child exploitation to become beggars in pilgrimage tourism areas. KH's grave. Sheikh Asnawi. A qualitative approach using the case study method was carried out to 5 informants, consisting of 3 child beggars, 1 person from one of the child beggar informants' parents, and 1 manager of the KH tomb pilgrimage tourism area. Sheikh Asnawi. Data collection was obtained through observation and through direct interviews. Test the validity of the data using data reduction, data display, and drawing conclusions. The results showed that of the 3 child beggar informants, 2 of them were victims of child exploitation to be used as beggars by their parents and had a tendency to have an impact on maladaptive behavior shown by children, the child factor was exploited by parents as beggars, namely low economic factors, supervision low parenthood, and the absence of applicable law enforcement. Exploitation of children leads to maladaptive behavior in children, therefore counseling using the Rational Emotive Behavior Therapy (REBT) technique should be given with the aim of reducing maladaptive behavior in children who are victims of parental exploitation.